Genetic testing: prediction vs. risk - Yeo, Giles (Henry Stewart Talks, 2020)
Genetic principles, ‘Traditional’ Sanger sequencing and how it led to development of high throughput sequencing, The principle underlying high throughput sequencing, Some applications of high throughput sequencing including obesity, The difference between risk vs. prediction in genetics